(untitled) (Transport systems and technologies, 2022)
The article presents the results of computer simulation of the strength of the improved design of the hatch cover of the gondola. A feature of the improvement is the production of a sheet of polymer composite material, and binding - from a U-shaped profile covered with a horizontal sheet. At the same time, the cross-sectional resistance of the improved strapping design relative to the transverse axis increases by 17.5% compared to a typical cross-section. It is important to say that the proposed hatch cover has a mass 12% lower than the typical design. To determine the main strength indicators of the proposed design of the hatch cover of the gondola, the calculation was performed for the main schemes of its load. It was found that, taking into account the proposed solutions, the maximum stresses in the sheet of the hatch cover are 25% lower than in the standard design, and in the binding - by 10%. The conducted researches will help to reduce damages of covers of hatches in operation and expenses for the maintenance of gondola cars, and also will be useful developments at designing of their modern designs.